Eugenol, a plant-derived phenolic nutraceutical, protects thiol (SH) group in myocardium from ROS-mediated oxidation under chemotherapeutic stress induced by arsenic trioxide – a in vivo model study. (3rd July 2018) - Binu, P.; Gifty, K.; Vineetha, R. C.; Abhilash, S.; Arathi, P.; Nair, R. Harikumaran
Abstract: Arsenic trioxide is an effective chemotherapeutic agent for the treatment of acute promyelocytic leukemia. The clinical usefulness of arsenic trioxide is narrow due to different organ toxicities. It is hypothesized that the generation of reactive oxygen species by arsenic trioxide leads to thiol-based oxidative damage in rat myocardium. In this study, the defensive effect of eugenol on thiol-based oxidative stress was investigated in arsenic trioxide-treated rats. Rats were orally administered with arsenic trioxide (4 mg/kg per day) alone and in combination with eugenol (5 mg/kg per day) for 30 days. Reduction in relative organ weight, total thiol level, protein thiol content, acid-soluble thiol content, thioredoxin activity, and protein content was witnessed in arsenic trioxide-treated rats. Additionally, the total antioxidant activity, tissue GSH level, and GSH/GSSG ratio were considerably diminished. However, the co-treatment of eugenol noticeably sheltered the arsenic trioxide-mediated cardiotoxicity. In conclusion, eugenol is a prospective phenolic compound, of natural origin, for protecting the thiol group in myocardium from oxidative stress by chemotherapeutic compounds.